THE EFFECT OF E-LEARNING ON STUDENTS’ ACHIEVEMENT IN UNIVERSITAS POTENSI UTAMA - Nurafifah Hasbi Nasution; Enni Maisaroh (Journal MELT (Medium for English Language Teaching), 2019)
It is believed that internet helps people to do better and faster. It has been used globally in almost every aspects of life. In education, internet is known as the golden key to intelligence, since it offers unlimited resource. It can be learning media in the classroom or while self-learning. Considered as an international language, English is used as main tool of communication on internet. It acts as the language of the instructions and language of the users. It is interesting to analyze its use by students in a developing country like Indonesia. In fact, Indonesia is one of the countries with millions internet users. As a result, e-learning becomes an option to deal with teaching learning process, especially for students of English department. By using internet, they can master certain topics and English themselves better. This study is quantitative research using pre-experimental design. It is aimed to analyze the effect of e-learning on achievement of students in Universitas Potensi Utama. The research result of this study was calculated by using Wilcox on test in which p-value is 0.462 and p> 0.05 which means the Null hypothesis is accepted. So it is concluded that there is no significant difference between e-learning and traditional learning. However, students have positive perceptions on e-learning because they argue that it can make them highly motivated to learn more about the subject.